The Impact of Diabetes Mellitus on Wound Healing in Breast Reconstruction. Issue 3 (March 2017) - Hart, Alexandra; Funderburk, Christopher D.; Chu, Carrie K.; Pinell-White, Ximena; Halgopian, Thomas; Manning-Geist, Beryl; Carlson, Grant; Losken, Albert
Abstract : Background: Although diabetes mellitus (DM) is a known risk factor for surgical complications in general, there is little published evidence to establish such an effect among patients undergoing breast reconstruction (BR). The purpose of this study was to assess the impact of DM on complications in patients undergoing postmastectomy BR. Methods: Patients who underwent BR at our institution from November 2002 to November 2012 were identified. Clinical and demographic data of patients with type 1 or type 2 DM were reviewed. Complications occurring within 60 days of surgery were compared between diabetic and nondiabetic patients for both autologous and nonautologous reconstruction types. Results: A total of 1371 BR were performed in 1035 patients. There were 877 (64.0%) autologous reconstructions and 494 (36.0%) implant-based reconstructions. Patients with DM (n = 64) had significantly higher preoperative blood glucose levels (137.5 vs 100.1, P < 0.05). Postoperatively, DM patients reconstructed with implants had a significantly higher incidence of delayed wound healing (22.2% vs 9.7%; P = 0.04). This was not observed in patients with DM reconstructed with autologous tissue (7.4% vs 6.6%; P = 0.70). Diabetic patients had a significantly higher incidence of hypertension and were older than nondiabetic patients. To control for these variables and other potential confounders, multiple logistic regression analysis was performed. Again, diabetic patients had a significantly higher incidence of delayed wound healing following implant-based reconstruction (odds ratio, 2.52, 95% confidence interval = 1.2–6.2) but not autologous reconstruction (odds ratio, 0.97; 95% confidence interval = 0.2–4.6). Conclusions: Diabetes heightens the risk of wound healing complications among patients undergoing implant-based reconstruction.